Carbon Nanotubes‐Based 3D Printing Ink for Multifunctional "Artificial Epidermis" with Long‐Term Environmental Stability. Issue 11 (28th April 2022) - Abodurexiti, Ayinuer; Maimaitiyiming, Xieraili
Abstract: 3D printing is a rapidly developing field because it has been widely used in the rapid design and manufacturing of flexible sensors to meet the needs of complex soft structures and devices. In this study, a composite hydrogel ink composed of polyvinyl alcohol, silk fibroin, conductive polymer, and carbon nanotubes is designed, and using 3D printing technology an "artificial epidermis" with long‐term environment stability and self‐healing ability is created. In addition, the "artificial epidermis" also has the multifunctional characteristics of sensing pressure, strain, temperature, and humidity. It has a wide pressure (0–165 kPa), strain (0–355%), temperature (−20–68 °C) and humidity (45–85%) sensing range and high sensitivity. While detecting the tiny movements of the human body, after self‐healing, the device can fully restore its sensing capabilities and perform accurate human monitoring. Furthermore, it can also monitor changes in temperature and humidity, distinguish between hot and cold water, and perform detection of water droplets. Customized 3D printing of flexible electronic devices has opened up new ways for the biological integration of various sensors in wearable electronic systems and the application of advanced bionic skin. Abstract : In this study, a composite hydrogel ink, using 3D printing technology is designed to create an "artificial epidermis" with long‐term environment stability and self‐healing ability. "Artificial epidermis" has the multifunctional characteristics of sensing pressure, strain, temperature, and humidity, while detecting the tiny movements of the human body.